Fieldwork Risks: Towards a Regimentation of Research? (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
Fieldwork in risky areas has become a subject of public debate, especially after the murder of the Italian PhD student Giulio Regeni. The essay starts by contextualising the origin and etymology of risk, which is related to the geographical explorations of the modern era, and by outlining the increasing securitisation of contemporary society. It then examines research mobility and protocols of risk assessment and management. The issue of civil liability of academic personnel and institutions is discussed in the light of Italian law. Finally, research and knowledge are approached not just as security matters but in terms of public interest.
Keywords: Fieldwork; Risk areas; Risk assessment; Risk management; Civil liability; Research freedom